Three cases of anaphylaxis following injection of a depot corticosteroid with evidence of IgE sensitization to macrogols rather than the active steroid. Issue 1 (10th January 2017) - Brandt, Nicolaj; Garvey, Lene H.; Bindslev‐Jensen, Ulla; Kjaer, Henrik Fomsgaard; Bindslev‐Jensen, Carsten; Mortz, Charlotte G.
Abstract: We present three cases with anaphylaxis after injection of a depot corticosteroid. First, the steroid was suspected as the elicitor, but after evaluation the excipient macrogol was found to be the elicitor. One of the patients had reactions to several unrelated drugs. Increased awareness of anaphylaxis to excipients such as macrogols is needed, especially when allergy tests for the active drug is negative and in patients with a history of repeated anaphylaxis to seemingly unrelated drugs. To establish the correct diagnosis it is important to test with the exact formulation of the culprit drug, as well as all the ingredients including excipients.